Historical and ethnographic region Slobozhanschina in historiographical research - Аксьонова, Наталя (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article provides an overview of the available historiographical works that characterize ethnographic sources and stages of ethnographic study of historical and ethnographic region Slobozhanschina . The author comes to the conclusion that the only ethnographic region Ukrainians, who does not have a holistic historiographical research is Slobozhanschina.